Common Injuries among Military Recruits in Selected Training Centers of Bangladesh Army - Chowdhury, Iqbal Bahar; Haque Khan, Manzurul (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Bangladesh army has a continuous process of recruit training throughout the year in its different training centers. While training, recruits suffer from a lot of health problems which hinders their physical training as well as academic activities. In this regard “Injury” is the main problem as identified. In Bangladesh, there is little data obtained as regard to the common injuries among recruits. Objectives: To ascertain common injuries of recruits in selected military training centers of Bangladesh Army. Materials and Methods: This cross-sectional, descriptive study was conducted from 01 July 2018 to 30 June 2019 at Chattogram Cantonment, Chattogram in two selected training centers of Bangladesh Army for the initial 06 months of the training period. The samples were selected purposively. Among 2702 study population the number of injured recruits (Respondents) was 152. A semi-structured pre-tested questionnaire and checklist were used as the research instrument. Results: Among the 152 respondents 65(42.8%) suffered from sprain, 43(28.3%) from shin pain, 20(13.2%) from fracture, 9(5.9%) from muscle strain, 6(3.9%) from low back-pain, and 9(6%) suffered from other different types of injuries. Conclusion: Further study is needed to conduct through out the full duration of the recruit training to ascertain more specifically the common injuries among the recruits in BD Army. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 3-6